THE COMPARISON ON RESULT OF LEARNING BETWEEN USING CONVENTIONAL LEARNING MODEL AND TEAM ACCELERATED INSTRUCTION SUBJECT DRAWING BUILDING CONSTRUCTION IN CLASS X TGB SMKN 2 SURAKARTA - Anggita Putri Iswari; Ernawati Sri Sunarsih; A.G. Thamrin (Universitas Sebelas Maret, 2017)
This research aims to kamislot (1) determine whether or not differences cognitivedomain between using Conventional learning model with Cooperative type TeamAccelerated Instruction model; (2) determine whether or not differences affective domainbetween using Conventional learning model with Cooperative type Team AcceleratedInstruction model; (3) determine whether or not differences psychomotor domain betweenusing Conventional learning model with Cooperative type Team Accelerated Instructionmodel on result of learning subject Drawing Building Construction in class X TGBSMKN 2 Surakarta School Year 2016/2017.This research includes experiment researchconducted in class X TGB A and class X TGB B. The sampling technique usednonprobability sampling with purposive sampling method. The collection of data carriedout by multiple choice test for data of student learning result in the cognitive andobservation for data of student learning result in the affective and psychomotor. The dataanalysis using wilcoxon test with significance level on 0.05. Is expressed equally ifp>0.05 and both of models are expressed differently if p<0.05. The result of thisresearch are as follows. First, there are differences on learning result between cognitivedomain using Conventional learning model and Cooperative type Team AcceleratedInstruction model that obtained probability value of 0.000< 0,05. Second, there aredifferences on learning result between affective domain using Conventional learningmodel and Cooperative type Team Accelerated Instruction model that obtainedprobability value of 0.000< 0.05. Third, there are differences on learning result betweenpsychomotor domain using Conventional learning model and Cooperative type TeamAccelerated Instruction model that obtained probability value of 0.002< 0.05.